Adams-Oliver syndrome, a successful conservative approach for a large scalp defect - Vera Baptista (Journal of Pediatric and Neonatal Individualized Medicine, 2015)
Adams-Oliver syndrome was first described in 1945 as a multiple congenital malformations association including aplasia cutis congenita and terminal transverse limb defects, along with cardiovascular and central nervous system anomalies. We report the case of a boy, prenatally diagnosed with a malformation of feet and right hand. At birth, a malformation of the skull was observed, at midline and right frontal, parietal and occipital region, with meningeal exposition. He presented with abnormal feet and right hand with hypoplastic fingers and also exhibiting cutis marmorata telangiectatica. Cardiac, abdominal and central nervous system malformations were excluded. He started a conservative approach based on daily dressings. The scalp defect closed at 4 months with this management strategy. At this age, a skull defect about 5 cm long was still perceptible by palpation of the area. The boy showed normal growth and neurologic development. No complications were reported. This report reinforces the effectiveness of conservative management strategies for extensive bone and epithelization defects in syndromes of aplasia cutis congenita like Adams-Oliver syndrome.